Numerical methods for engineers : with programming and software applications - Chapra, Steven C.; Canale, Raymond P. (Boston : WCB/McGraw-Hill, 1998)
Accompanying computer disk includes a Windows version of Numerical methods electronic toolkit
BIBINDX
System requirements: IBM or compatible PC; Windows 3.1 or above
Keywords: Engineering mathematics -- Data processing; Numerical calculations -- Data processing; Microcomputers -- Programming